1986
DOI: 10.1016/0014-5793(86)81225-x
|View full text |Cite
|
Sign up to set email alerts
|

Segment α 182‐198 of Torpedo californica acetylcholine receptor contains a second toxin‐binding region and binds anti‐receptor antibodies

Abstract: The area around is thought to be a functionally important part of the cc-subunit of the acetylcholine receptor. We have synthesized peptide ct182-198 of the a-chain of the Torpedo californica acetylcholine receptor and investigated the binding to the peptide of a-bungarotoxin, cobratoxin and antibodies raised against acetylcholine receptor. The results showed that the synthetic peptide ~~182-198 contains a second toxin-binding region and also binds a considerable fraction of anti-receptor antibodies. We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
1

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 26 publications
4
37
1
Order By: Relevance
“…[6] and [3H]MPTA (this study) on the reduced AChR. It has also been reported that synthetic peptides corresponding to this region of the o~-chain can bind or-toxins [26][27][28], albeit with low affinities and in an agonist-insensitive manner. The present finding that the majority of the incorporated [3H]DDF was associated with the fragment ot 179-207 shows that residues located within this region are actually involved in the binding of cholinergic ligands in the native AChR.…”
Section: Discussionsupporting
confidence: 55%
“…[6] and [3H]MPTA (this study) on the reduced AChR. It has also been reported that synthetic peptides corresponding to this region of the o~-chain can bind or-toxins [26][27][28], albeit with low affinities and in an agonist-insensitive manner. The present finding that the majority of the incorporated [3H]DDF was associated with the fragment ot 179-207 shows that residues located within this region are actually involved in the binding of cholinergic ligands in the native AChR.…”
Section: Discussionsupporting
confidence: 55%
“…The toxin-binding site(s) also resides in the a subunit of AcChoR (6). Recent studies from this laboratory using synthetic uniform-sized overlapping peptides encompassing the entire extracellular parts of the a chain of human AcChoR and Torpedo AcChoR enabled the localization of the full profile of the toxin-binding regions on the Torpedo (7)(8)(9) and human (10) receptors. Conversely, the binding sites for AcChoR on a-bungarotoxin (a-BTX) were mapped by synthetic peptides representing each of the a-BTX loops (11,12).…”
mentioning
confidence: 99%
“…Although the AChR a-subunit's identity as the immunodominant subunit of the receptor has been noted (21)(22)(23)(24), only recently by using synthetic peptides (5)(6)(7)(8)(9) have specific functional domains been identified. Such studies showed that residues around 192-193 of the AChR a-subunit from Torpedo californica include an a-BuTx binding site (5)(6)(7)(8)(9), although the same sequence from the HuAChR is not reactive with a-BuTx (6). Our studies, using affinity-purified autoantibodies to HuAChR a-subunit 157-170 from MG patient sera, show that this antibody significantly blocked the binding of a-BuTx to cultured rat muscle cells (myotubes).…”
Section: Discussionmentioning
confidence: 99%
“…tion with a-bungarotoxin (a-BuTx) (5)(6)(7)(8)(9). These interactions also map accessible sites on AChR that bind antibodies.…”
Section: Introductionmentioning
confidence: 99%